POST-SOCIALIST URBAN FINANCIALIZATION IN SERBIA: AN EMPIRICAL INSIGHT - Zeković, Slavka (The European Journal of Applied Economics, 2024)
Financialization as a global process usually promotes finance as a dominant narrative (Aalbers, 2019) and  plays a strong role in the economic development and urban changes in all contextual frameworks. Nevertheless, research on financialization is relatively scarce in post-socialist European countries, with a complete absence of research on this issue in Serbia. Focusing on post-socialist Serbia in the post-crisis  period (after 2008), the paper situates the narrative of urban financialization into the broader context by: illuminating the financialization dimensions; identifying the indicators for selected financialization dimensions; analyzing concrete data for selected financialization dimensions by specific indicators, and comparing available indicators of financialization with those in some post-socialist countries of CEE and SEE. The empirical analysis provides insight into the complex nature of urban financialization which is measured by specific indicators at the national level.
Keywords: financialization, commercial and residential properties, urban financialization, post-socialist countries, Serbia